Sistem Informasi Manajemen Pada Puskesmas Kota Jayapura Berbasis Web - Andrian Sah; Jusmawati Jusmawati; Siti Nurhayati; Mursalim Tonggiroh; Septinus Bonay (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
The North Jayapura Public Health Center, which is one of the health service centers, is one of the health institutions that is being developed. The North Jayapura Health Center handles a large number of patients and this causes serious problems in obtaining information about patients, patient visits for treatment, patient medical records and also data on drugs that have been used by the health center. In addition to the problem of patient data collection and archiving medical records is an important thing that needs to be considered. Moreover, at the Puskesmas, patient data collection, starting from patient registration and archiving patient medical records, is still done manually, meaning that everything is still written on piles of paper and stored on storage shelves, so that when the puskesmas needs patient data, visit reports , as well as data reports of drugs that have been used, it takes a long time to find where the data is stored. The Jayapura City Health Center management information system application that was created can be used to assist the Jayapura City Health Center in the patient service process, patient data collection, drug data collection and others. Admin can operate all the functions in this system. Pharmacists can carry out the drug data collection process and provide prescriptions. Doctors can give medicine, make diagnoses and actions.